General description of the Bulungan Research Project - Machfudh (Center for International Forestry Research, 2002)
This chapter presents the introduction of the natural resources of the study area of the Bulungan Research Project. It covers information on topography, climate, hydrology, geology, soils, forest types, and socio-economic conditions of local people as well as the economic development plan of the local government in the area. Coloured maps of the research locations and statistical data are included.